P95 Cost effectiveness of overnight face-to-face nurse led COPD service. (2nd December 2011) - Green, D; Hampson, O; Agarwal, S; Church, S
Abstract : Background: Prevalence of Chronic Obstructive Pulmonary Disease (COPD) is twice the UK average with emergency admission rate 175% higher in Knowsley Primary Care Trust (PCT). A primary care nurse led COPD service was initially operational from 08:00 to 10:00, thereafter telephone advice was available overnight for management of patients with exacerbation of COPD. This was later commissioned by the PCT to provide a 24 h, 365 days face-to-face rapid response contact assessment at home or in the Accident and Emergency department. The Nurses were contracted to assess the patients within 2 h of the contact. Following this, staffing levels needed to be considerably increased. This development led to an increased burden on the COPD service. Aim: To assess the cost-effectiveness of the this new service provision as contracted to direct further commissioning and planning within the restricted budget. Methods: A database of patients with confirmed diagnosis of COPD was setup. The database included 3500 patients. They were provided with contact numbers in an event of exacerbation. Activity was monitored over 24 h from September 2009 to July 2010 (10 month's duration). Data were analysed using Excel. Results: 399 contacts made over the study period. The majority of the first contacts (18%) were on Mondays during the day hours. Another 17% first contacts were made over the weekends. 62 patients (15%) made contact overnight from 23:00 to 08:00 over the 10 months duration. Only 17 home visits were required and 45 patients reviewed in A&E. Of the patients reviewed in A&E only five were suitable for supported discharge. Conclusion: Overnight face-to-face COPD nurse led service was not found to be cost-effective. This provides valuable information to inform the COPD national strategy consultation in development for further services.